Government Responsibility Towards Handling Investment Conflicts In Central Java - Nazmudin Nazmudin; Mohamad Yusup; Dian AM (ijd-demos, 2026)
Abstract The purpose of this study is to improve understanding of the importance of government responsiveness in handling investment conflicts in Central Java. To determine the efforts made by the Central Java government to improve its responsiveness in handling investment conflicts. To analyze the level of responsiveness of public complaint services regarding investment in Central Java which is experiencing a decline and is hampered by the problem of expensive land. The research method used is descriptive qualitative with an empirical field study approach. Data collection was carried out through observation, interviews, and documentation studies on the implementation of Law Number 25 of 2007 concerning Investment in Central Java. The results show that the responsiveness of the Central Java Provincial Government in resolving investment conflicts rests on the capabilities of proactive and mediative regional leadership. The escalation of land dispute conflicts was successfully reduced through a strategy of standardizing land value zoning, optimizing the Integrated Industrial Zone (KIT), and implementing an inclusive compensation scheme based on the "compensation for profit" concept that empowers the economy of affected residents. The integration of accountable services and transparency of public information has proven effective in minimizing information asymmetry and social resistance at the grassroots level. The conclusion of the study confirms that the level of regional leadership is the main determining factor in the success of investment conflict management, but its sustainability requires the institutionalization of an early warning system so that it does not only depend on the figure of the regional head alone. Keywords: Government Responsiveness, Investment Conflict, Land Obstacles, Regional Leadership, Central Java. Keywords: Conflict, Investment, Central Java. Abstrak Tujuan penelitian ini adalah untuk meningkatkan pemahaman mengenai pentingnya responsivitas pemerintah dalam menangani konflik investasi di Jawa Tengah, serta mengidentifikasi upaya yang dilakukan pemerintah Jawa Tengah untuk meningkatkan responsivitas tersebut. Penelitian ini juga menganalisis tingkat responsivitas layanan pengaduan publik terkait investasi di Jawa Tengah, yang saat ini mengalami penurunan kinerja dan terkendala oleh masalah tingginya harga lahan. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan studi lapangan empiris. Pengumpulan data dilakukan melalui observasi, wawancara, dan studi dokumentasi mengenai pelaksanaan Undang-Undang Nomor 25 Tahun 2007 tentang Penanaman Modal di Jawa Tengah. Hasil penelitian menunjukkan bahwa responsivitas Pemerintah Provinsi Jawa Tengah dalam menyelesaikan konflik investasi sangat bergantung pada kapabilitas kepemimpinan daerah yang proaktif dan mediatif. Eskalasi konflik sengketa lahan berhasil diredam melalui strategi standardisasi zonasi nilai lahan, optimalisasi Kawasan Industri Terpadu (KIT), serta penerapan skema kompensasi inklusif berbasis konsep "kompensasi untuk keuntungan" (*compensation for profit*) yang memberdayakan ekonomi warga terdampak. Integrasi layanan yang akuntabel dan transparansi informasi publik terbukti efektif dalam meminimalkan asimetri informasi serta resistensi sosial di tingkat akar rumput. Kesimpulan penelitian menegaskan bahwa kualitas kepemimpinan daerah merupakan faktor penentu utama keberhasilan pengelolaan konflik investasi; namun, keberlanjutannya memerlukan pelembagaan sistem peringatan dini agar tidak semata-mata bergantung pada sosok kepala daerah. Kata kunci: Responsivitas Pemerintah, Konflik Investasi, Kendala Lahan, Kepemimpinan Daerah, Jawa Tengah. Kata kunci: Konflik, Investasi, Jawa Tengah.